2019
DOI: 10.1055/s-0039-1696649
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma is the second most common primary liver cancer but represents only a small portion of all primary liver cancers. At the time of diagnosis, patients are often not surgical candidates due to tumor burden of other comorbidities. In addition, there is a very high rate of tumor recurrence after resection. Local regional therapies, specifically ablative therapies of radiofrequency ablation, microwave ablation, cryoablation, and irreversible electroporation, have proven to be beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Microwave ablation (MWA) evolved as an alternative to RFA that allows for larger ablation zones and can be used in tissues in which RFA would not be successful, such as charred desiccated tissue [32,33]. The largest retrospective study consisting of 107 patients with primary or recurrent iCCA who underwent MWA found an OS at 1, 3, and 5 years of 93.5%, 39.6%, and 7.9%, respectively [34].…”
Section: Microwave Ablationmentioning
confidence: 99%
See 2 more Smart Citations
“…Microwave ablation (MWA) evolved as an alternative to RFA that allows for larger ablation zones and can be used in tissues in which RFA would not be successful, such as charred desiccated tissue [32,33]. The largest retrospective study consisting of 107 patients with primary or recurrent iCCA who underwent MWA found an OS at 1, 3, and 5 years of 93.5%, 39.6%, and 7.9%, respectively [34].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Irreversible electroporation (IRE) is a newer form of ablative technology that uses a high electrical voltage rather than thermal-based ablation such as RFA, MWA, and cryoablation [33]. There is a lack of data for IRE due to the small amount of unresectable primary or recurrent iCCAs that meet criteria for IRE treatment.…”
Section: Irreversible Electroporationmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20]. However, RFA has recently emerged as a minimally invasive treatment option for hepatic malignancies and as an alternative to resection, especially for patients who have small lesions and/or are unfit for surgical resection [21]. With regard to size, some authors consider RFA a useful technique to provide local control of small, localized, unresectable lesions; in patients with hepatocellular carcinomas (HCCs) 2 cm, for instance, RFA is considered an alternative to hepatic resection because of their comparable long-term efficacy [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that cryoablation provides an option for hepatic tumors, but compelling evidence for CCA remains insufficient. Further studies focusing on cryoablation of CCA may help demonstrate its role in a select group of patients where resection or other ablative therapies are not possible ( 103 ).…”
Section: Interventional Treatment For Ccamentioning
confidence: 99%